177k views
1 vote
IF F(x) =3x+2 and g(x)=-4x-1

then find
1. F(3) =
2. (F+g)(x)
3. g(x) - F(x)
4. (F • F)(x)
5. F(x)/g(x)
6.g(open circle)g

User Nethken
by
4.8k points

1 Answer

5 votes

Answer:

1) 11

2) -x+1

3) -7x-3

4) 9x+8

5) (3x+2)/(-4x-1)

6) 16x+3

Explanation:

1) F(3)=3×(3)+2=9+2=11

F(3)=11

2) (F+g)(x)=(3x+2)+(-4x-1)=(-x+1)

(F+g)(x)= -x+1

3) g(x)-F(x)=(-4x-1)-(3x+2)=(-7x-3)

g(x)-F(x)= -7x-3

4) (F • F)(x)=3(3x+2)+2=9x+6+2=9x+8

(F • F)(x)= 9x+8

5) F(x)/g(x)=


(3x + 2)/( - 4x - 1)


- ((3x + 2)/(4x + 1) )

6.g(open circle)g= -4(-4x-1)-1=16x+4-1=16x+3

g(open circle)g= 16x+3

I hope it helped you

User Matt Foley
by
5.0k points